PENERAPAN METODE CRITICAL PATH METHOD (CPM) PADA PENJADWALAN REPARASI KAPAL PATROLI XVI 2012 - Mandaku, Hanok; Afifudin, M. Thezar; Parera, Gloria C. (Jurnal Mitra Teknik Industri, 2024)
Ship repair work at shipyard facilities at the Ship Repair Laboratory, Faculty of Engineering, Pattimura University has not implemented project scheduling methods to optimize performance. Determining the time and scheduling of ship repair work is still done based on experience alone. As a result, time and cost inefficiencies occur which result in low performance, making it difficult for the docking and shipping industry to develop and contribute to the development of the maritime sector. This research aims to optimize the 2012 XVI Patrol Ship repair schedule. The method used in this research is the Critical Path Method (CPM). The object of the research is Patrol Ship XVI 2012. The research results show that the repair work process in existing conditions contains 24 activities and 21 routes which require 50.25 hours of work time. Rescheduling with CPM produces a critical path with 10 activities and 9 paths that require a processing time of 22.5 hours, or there is an efficiency of 44%. These results prove that CPM has succeeded in optimizing ship repair work time. These findings are useful for the Ship Repair Laboratory, Faculty of Engineering, Pattimura University to optimize performance to support the development of Indonesia's maritime sector.